Pengaruh Supervisi Kepala Sekolah terhadap Kinerja Guru di SD Negeri 2 Candirenggo Singosari Malang - Suprapti, Yuni (FKIP Universitas Wisnuwardhana, 2022)
This study aims to determine the effect of the principal's supervision on teacher performance at SD Negeri 2 Candirenggo Singosari Malang. This research uses descriptive quantitative methods and approaches. The subjects of this study were 10 teachers at SD Negeri 2 Candirenggo Singosari Malang. The main data collection technique uses a questionnaire. Interview techniques were carried out to support the results of the questionnaire data. The informants in the interviews in this research were the Principals and Teachers. The results showed that the value of tcount was 3,303 and ttable was 2,262, because tcount> ttable, then H0 was rejected, H1 was accepted. Thus there is sufficient influence between the influence of the principal's supervision on teacher performance at SD Negeri 2 Candirenggo Singosari Malang.